2007
DOI: 10.1016/j.mee.2007.04.029
|View full text |Cite
|
Sign up to set email alerts
|

SrHfO3 as gate dielectric for future CMOS technology

Abstract: Thin epitaxial films of the high-perovskite SrHfO 3 were grown by molecular beam epitaxy on Si(100) and investigated by ellipsometry and X-ray photoelectron spectroscopy to determine its band gap and valence band offset. Conducting AFM shows a good correlation between topography and current mapping, pointing to direct tunneling conduction. Long channels MOSFETs with low equivalent oxide thickness (EOT) were fabricated and their channel mobility measured. Mobility enhancement can be achieved by post processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
40
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 13 publications
5
40
1
1
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32] In some early work, crystalline SHO was investigated as a future gate dielectric material for Sibased devices. 25,27 The SHO films were grown by molecular beam epitaxy (MBE) on Si (001) despite the 6% lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30][31][32] In some early work, crystalline SHO was investigated as a future gate dielectric material for Sibased devices. 25,27 The SHO films were grown by molecular beam epitaxy (MBE) on Si (001) despite the 6% lattice mismatch.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] In some early work, crystalline SHO was investigated as a future gate dielectric material for Sibased devices. 25,27 The SHO films were grown by molecular beam epitaxy (MBE) on Si (001) despite the 6% lattice mismatch. The electrical performance of epitaxial SHO on Si showed low equivalent oxide thickness (EOT) of 0.7 nm and low leakage current (10 À6 A/cm 2 ) at À1 V. 25 However, the relatively high D it ($10 13 eV À1 cm À2 ) likely contributed to the poor mobility of the SHO/Si field-effect transistors (FETs), where both n-FETs and p-FETs exhibited carrier mobilities of $25 cm 2 /V-s at 1 MV/cm.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite structured hafnium compounds doped with various dopants were reported as good luminescent materials [6][7][8] and scintillating materials for their potential impact in high energy nuclear medical applications [9]. Recently SrHfO 3 was reported as a potential material for future CMOS technology [10]. Strontium based ABO 3 perovskites such as SrZrO 3 and SrHfO 3 adopts orthorhombic structures at room temperatures, undergoes a series of structural variation and becomes cubic at elevated temperatures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, IBM research team with their collaborators [9,10] has demonstrated that thin SrHfO 3 films grown by molecular beam epitaxy on Si(001) exhibited good physical and electrical properties and proposed that SrHfO 3 -based n-and p-MOSFETs could be fabricated with EOT down to 0.7 nm. This promising application of SrHfO 3 is attributed to the key advantages that the optical band gap of SrHfO 3 film is 6.1 ± 0.1 eV [9][10][11], which is wider than that of SrTiO 3 (3.5 eV), the resulting valence band offset of SrHfO 3 with respect to Si is 3.0 ± 0.1 eV [9,10], and thus a conduction band offset of 2.3 eV for SrHfO 3 /Si system could be achieved. In view of SrHfO 3 as a highly promising dielectric gate in MOSFET application, it is of great Recently, SrHfO 3 compound was proposed as a potential gate dielectric to fabricate metal -oxide -semiconductor field-effect transistors (MOSFET) with equivalent oxide thickness (EOT) below 1 nm.…”
mentioning
confidence: 99%